Beitrag zur Korrektur der Zentralen Venösen Hypertension Nach der Anlage einer Arteriovenösen (AV) Fistel zur Hämodialyse - Bachleda, P; Utíkal, P; Köcher, M; Zadrazil, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1999)
Stenosis or thrombosis of the central venous tract (axillaris or subclavian vein) may be after creation of arteriovenous fistula for hemodialysis the cause of manifestation of venous hypertension. The authors evaluate positive bypass to internal jugular vein in the therapy of this complication.
Keywords: Hypertension; arteriovenózní zkrat; Retrospective Studies; vena subclavia; lidé středního věku; lidé; ženské pohlaví; vena axillaris; Renal Dialysis; retrospektivní studie; venae jugulares; žilní trombóza; Female; mužské pohlaví; dialýza ledvin; Adult; Middle Aged; hypertenze; Jugular Veins; Axillary Vein; Humans; dospělí; Male; Venous Thrombosis; Arteriovenous Shunt, Surgical; Subclavian Vein